Penalaran Hukum Dalam Proses Mengadili Perkara Pidana Dalam Kerangka Kebebasan Hakim - J. Pajar Widodo (PRANATA HUKUM, 2011)
Judge freedom clings on individual judge in running his/her functions brings a judge, basis bound judge freedom minimum verification and judge confidence, as base law reasonable deductive reasoning towards .fact, so that has legal formal. Legal reasoning has deductive - reasonable, produce formal justice, that is justice based on law. Judge freedom quality enhanced with fact induction reasoning normatif - science- religious, based on principle kontigensi creative law alive at society, legal reasoning in course of bring to justice has inductive that laid law live as premis fortunate, will produce justice enthusiasm substantive justice that is existing justice in society.